2018
DOI: 10.1074/jbc.m117.816272
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the 14-3-3ζ interactome reveals critical roles of RNA-splicing factors during adipogenesis

Abstract: Adipogenesis involves a complex signaling network requiring strict temporal and spatial organization of effector molecules. Molecular scaffolds, such as 14-3-3 proteins, facilitate such organization, and we have previously identified 14-3-3ζ as an essential scaffold in adipocyte differentiation. The interactome of 14-3-3ζ is large and diverse, and it is possible that novel adipogenic factors may be present within it, but this possibility has not yet been tested. Herein, we generated mouse embryonic fibroblasts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 53 publications
6
36
0
Order By: Relevance
“…We previously reported essential roles of one of the seven mammalian isoforms, 14-3-3ζ, in adipogenesis, as systemic deletion of 14-3-3z in mice resulted in significant reductions in visceral adipose tissue mass and decreased expression of mature adipocyte markers in gonadal adipocytes (34). Furthermore, through the use of proteomics to elucidate the 14-3-3z interactome, we found that 14-3-3z is necessary for RNA splicing during adipocyte differentiation (42). However, whether 14-3-3ζ can also influence metabolic processes specific to mature adipocytes has not been fully examined.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…We previously reported essential roles of one of the seven mammalian isoforms, 14-3-3ζ, in adipogenesis, as systemic deletion of 14-3-3z in mice resulted in significant reductions in visceral adipose tissue mass and decreased expression of mature adipocyte markers in gonadal adipocytes (34). Furthermore, through the use of proteomics to elucidate the 14-3-3z interactome, we found that 14-3-3z is necessary for RNA splicing during adipocyte differentiation (42). However, whether 14-3-3ζ can also influence metabolic processes specific to mature adipocytes has not been fully examined.…”
Section: Introductionmentioning
confidence: 86%
“…3T3-L1 cells were maintained in DMEM (Life Technologies Corporation, Grand Island, NY), supplemented with 10% newborn calf serum (NBCS) and 1% penicillin/streptomycin (P/S) and were seeded onto 12-well plates (100,000 cells/well) or 10cm dishes (2x10 6 cells/dish) 2 days prior to the induction of differentiation. Confluent cells were treated with a differentiation cocktail (DMEM supplemented with 10% FBS, 1% P/S, 500 μM IBMX, 500 nM dexamethasone and 172 nM insulin) for 48 hours, followed by media replacement (DMEM with 10% FBS, 1% P/S and 172 nM insulin) every 2 days for 7-8 days (34,42). Knockdown and overexpression of 14-3-3ζ was achieved by transfecting day 7-8 differentiated cells with scrambled control siRNA, 14-3-3ζ-specific siRNA (Ambion, Austin, TX), GFP control plasmids, or plasmids encoding 14-3-3ζ (14-3-3ζ IRES-GFP) using the Amaxa Cell Line Nucleofector Kit L, as per manufacturer's instructions (Lonza, Koln, Germany).…”
Section: Cell Culture and Transient Transfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from cells and tissues using the RNeasy Mini kit or the RNeasy Plus Mini Kit (Qiagen, Montreal, Quebec, Canada respectively, and stored at - Relative gene expression was normalized to the reference gene, Hprt, as previously described [18,24]. For a complete list of primers and their respective sequences, please see Supplemental Table 2.…”
Section: Rna Isolation and Quantitative Pcrmentioning
confidence: 99%
“…14-3-3ζ is a member of the 14-3-3 scaffold protein family, which are highly conserved serine and threonine binding proteins present in all eukaryotes [15][16][17][18]. They bind to a diverse number of enzymes, signalling proteins, and transcription factors and have been implicated in the regulation of numerous cellular processes, including proliferation, protein trafficking, and apoptosis [16,17].…”
Section: Introductionmentioning
confidence: 99%